2010
DOI: 10.1111/j.1464-5491.2010.03113.x
|View full text |Cite
|
Sign up to set email alerts
|

Telephone follow‐up to improve glycaemic control in patients with Type 2 diabetes: systematic review and meta‐analysis of controlled trials

Abstract: The analysis suggested that telephone follow-up interventions following a more intensive targeted approach could have a positive impact on glycaemic control for Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 33 publications
4
73
0
2
Order By: Relevance
“…Our findings for HbA 1c level were at the lower end of what might be expected based on the review by Wu et al (15), which reported a standardized weighted mean difference of 20.44 (95% CI 20.93 to 0.06) (i.e., an effect that is estimated as moderate but could plausibly be anywhere between no effect and a large beneficial effect). The review also showed that the interventions were not consistent in their impact on HbA 1c level (i.e., significant heterogeneity).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our findings for HbA 1c level were at the lower end of what might be expected based on the review by Wu et al (15), which reported a standardized weighted mean difference of 20.44 (95% CI 20.93 to 0.06) (i.e., an effect that is estimated as moderate but could plausibly be anywhere between no effect and a large beneficial effect). The review also showed that the interventions were not consistent in their impact on HbA 1c level (i.e., significant heterogeneity).…”
Section: Discussionmentioning
confidence: 60%
“…Since the onset of this 5-year LWWD trial, a number of studies of telephonedelivered interventions to improve glycemic control in patients with type 2 diabetes have been published and are summarized in a meta-analysis (15). Our findings for HbA 1c level were at the lower end of what might be expected based on the review by Wu et al (15), which reported a standardized weighted mean difference of 20.44 (95% CI 20.93 to 0.06) (i.e., an effect that is estimated as moderate but could plausibly be anywhere between no effect and a large beneficial effect).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the retrospective audit, to some degree, identified the rest of the frequent users as a group of physically and/or psychologically fragile patients, whose needs were not covered by ATC. This finding indicates that this specifically vulnerable group require more advanced and tailored interventions delivered by professionals who in addition to their diabetes qualifications are specialised in the care of vulnerable people, as also recommended in other studies [25,26]. The qualitative observations in this study provided an overview that was not available before and pinpointed the diversity of advice and recommendations given by the DSNs.…”
Section: Discussionmentioning
confidence: 61%
“…Forbes, Griffiths, Milligan, and While (2010) [17] study focused on telephone follow-up to improve glycemic control in patients with type 2 diabetes. The analysis of the study suggested that telephone follow-up interventions following a more intensive targeted approach could have a positive impact on the glycemic control for type 2 diabetes.…”
Section: Telephone Follow-up Callsmentioning
confidence: 99%